A self-assembled nanoplatform based on Ag2S quantum dots and tellurium nanorods for combined chemo-photothermal therapy guided by H2O2-activated near-infrared-II fluorescence imaging. (1st March 2022) - Li, Chao-Qing; Ma, Meng-Wen; Zhang, Bin; Chen, Wei; Yin, Zhong-Yuan; Xie, Xiao-Ting; Hou, Xiao-Lin; Zhao, Yuan-Di; Liu, Bo
Abstract: A nanoplatform based on Ag2 S quantum dots (QDs) and tellurium nanorods (TeNRs) was developed for combined chemo-photothermal therapy guided by H2 O2 -activated near-infrared (NIR)-II fluorescence imaging. Polypeptide PC10 AGRD-modified TeNRs and Ag2 S QDs were co-encapsulated in 4T1 cell membrane to prepare a nanoplatform (CCM@AT). Ag2 S QDs and TeNRs in the CCM@AT were used as a fluorescence probe and photosensitizer, and a chemotherapeutic prodrug and quenching agent to quench the fluorescence of Ag2 S QDs, respectively. After the CCM@AT was specifically targeted to the tumor site, the TeNRs were dissolved by the high concentration of H2 O2 at the tumor site to light up the fluorescence of Ag2 S QDs for NIR-II fluorescence imaging. In addition, the generated toxic TeO6 6− molecules decreased ATP production by selective cancer chemotherapy, which is beneficial for photothermal therapy. The elevated temperature due to photothermal therapy in turn promoted the chemical reaction in chemotherapy. In vitro and in vivo toxicity results showed that the CCM@AT possesses high biocompatibility. Compared to single photothermal therapy and chemotherapy, the synergistic chemo-photothermal therapy can effectively suppress the growth of 4T1 tumor. This all-in-one nanoplatform provides a boulevard for the combination therapy of tumors guided by NIR-II fluorescence imaging. Statement of significance: NIR-II fluorescence imaging shows the characteristics of low tissue absorption, reflection, and scattering, which can greatly reduce the influence of autofluorescence in vivo . However, the non-negligible effect of autofluorescence is still observed in fluorescence imaging in vivo . Therefore, there is an urgent need to develop a strategy of controlled release of fluorescence for accurate imaging and tumor therapy. Here, Ag2 S quantum dots (QDs) with NIR-II fluorescence emission and good photothermal conversion efficiency are used as a fluorescence probe and photosensitizer, and tellurium nanorods (TeNRs) are used as a chemotherapeutic prodrug and quenching agent to quench the fluorescence of Ag2 S QDs. This multiple nanoplatform provides an inspiration for the combination therapy of tumor guided by NIR-II fluorescence imaging. Graphical abstract: Image, graphical abstract